Eduardo Blanco Amor Reviews the Collection of Poems Entre el clavel y la espada by Rafael Alberti - Tinnell, Roger (Madrygal. Revista de Estudios Gallegos, 2021)
Transcription and notes to the review article published by Eduardo Blanco Amor, article (published in the Venezuelan daily El Nacional in 1954) on Rafael Alberti’s Entre el clavel y la espada.